(untitled) (World Bulletin of Social Sciences, 2023)
In the course of the development of social partnership, the characteristics of the system of social partnership in each country are determined depending on its social orientation and level. Social partnership serves to balance the interests of society, to harmonize the interests of state and non-state organizations. That is, it applies the socio-political relations of citizens between the state and non-governmental organizations to the social life of the society based on democratic principles. In Uzbekistan, the best practices of developed foreign countries are being thoroughly studied in the application of social partnership relations to sociopolitical life. The model of social partnership in our country is aimed at ensuring the rights and interests and freedoms of all levels of social life. The model of social partnership implemented in Uzbekistan, the advanced methods of the models of foreign countries that have reached the stage of development have been studied on a scientific and creative basis. In our country, social partnership is considered primarily as a means of ensuring the development of society, resolving labor relations peacefully, and eliminating social tensions